Elaboration of the Method of Interpretation of the Qur'an: A Discourse on the Development of the Limitations of the Ijmāli Interpretation Method - Muhamad Khabib Imdad; Rizki Maulana Putra; Eni Zulaiha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research examines in depth the methodology of interpreting the Al-Qur’an by focusing on the elaboration of the ijmāli interpretation method. Tafsir ijmāli, as a method of interpreting the Al-Qur’an, offers a concise and global approach in understanding the meaning of the verses of the Al-Qur’an. The main aim of this research is to analyze the characteristics, advantages and challenges in applying the ijmāli interpretation method, as well as offering a discourse on the development of this method. The methodology used in this research is descriptive qualitative with a literature study approach. Primary data was obtained from tafsir books that use the ijmāli method as well as various literature about this tafsir method. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the research show that the ijmāli exegesis method has the advantage of presenting the meaning of the Al-Qur’an practically and is easily understood by various groups. However, this method also faces challenges in elaborating the deeper and more complex meaning of certain verses. The conclusion of this research confirms that the ijmāli exegesis method remains relevant and important in contemporary Al-Qur’an interpretation discourse, but needs to be integrated with other interpretive methods to provide a more comprehensive understanding of the Al-Qur’an. It is hoped that this research can contribute to the development of the methodology for interpreting the Al-Qur’an and enrich the treasures of interpretive science through the offerings provided.